Dental cell type atlas reveals stem and differentiated cell types in mouse and human teeth - Jan Krivanek (Nature Portfolio, 2020)
Unlike human teeth, mouse incisors grow throughout life, based on stem and progenitor cell activity. Here the authors generate single cell RNA-seq comparative maps of continuously-growing mouse incisor, non-growing mouse molar and human teeth, combined with lineage tracing to reveal dental cell complexity.